New tools to monitor Pseudomonas aeruginosa infection and biofilms in vivo in C. elegans - Xue, Feng; Ragno, Martina; Blackburn, Sarah A.; Fasseas, Michael; Maitra, Sushmita; Liang, Mingzhi; Rai, Subash; Mastroianni, Giulia; Tholozan, Frederique; Thompson, Rachel; Sellars, Laura; Hall, Rebecca; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionAntimicrobial resistance is a growing health problem. Pseudomonas aeruginosa is a pathogen of major concern because of its multidrug resistance and global threat, especially in health-care settings. The pathogenesis and drug resistance of P. aeruginosa depends on its ability to form biofilms, making infections chronic and untreatable as the biofilm protects against antibiotics and host immunity. A major barrier to developing new antimicrobials is the lack of in vivo biofilm models. Standard microbiological testing is usually performed in vitro using planktonic bacteria, without representation of biofilms, reducing translatability. Here we develop tools to study both infection and biofilm formation by P. aeruginosa in vivo to accelerate development of strategies targeting infection and pathogenic biofilms.MethodsBiofilms were quantified in vitro using Crystal Violet staining and fluorescence biofilm assays. For in vivo assays, C. elegans were infected with P. aeruginosa strains. Pathogenicity was quantified by measuring healthspan, survival and GFP fluorescence. Healthspan assays were performed using the WormGazerTM automated imaging technology.ResultsUsing the nematode Caenorhabditis elegans and P. aeruginosa reporters combined with in vivo imaging we show that fluorescent P. aeruginosa reporters that form biofilms in vitro can be used to visualize tissue infection. Using automated tracking of C. elegans movement, we find that that the timing of this infection corresponds with a decline in health endpoints. In a mutant strain of P. aeruginosa lacking RhlR, a transcription factor that controls quorum sensing and biofilm formation, we find reduced capacity of P. aeruginosa to form biofilms, invade host tissues and negatively impact healthspan and survival.DiscussionOur findings suggest that RhlR could be a new antimicrobial target to reduce P. aeruginosa biofilms and virulence in vivo and C. elegans could be used to more effectively screen for new drugs to combat antimicrobial resistance.